2015
DOI: 10.1152/ajpheart.00239.2014
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prophylactic flavan-3-ol in permanent focal ischemia in 12-mo-old mice

Abstract: Leonardo CC, Mendes M, Ahmad AS, Doré S. Efficacy of prophylactic flavan-3-ol in permanent focal ischemia in 12-mo-old mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…EC-treated ischemic WT mice displayed a reduction of forelimb motor coordination impairments associated with reduced anatomical injury and microglia/macrophage activation in pMCAO and tMCAO models of adult WT mice, impairments which were abolished in tissues and neurons from Nrf2 −/− mice (Shah et al, 2010 ). Interestingly, this neuroprotection was observed in 12 month-old WT and Nrf2 −/− mice, indicating that age influences Nrf2 function (Leonardo et al, 2013 , 2015 ).…”
Section: Nrf2 Targeted Intervention In Ischemic Stroke—advancements Fmentioning
confidence: 95%
See 2 more Smart Citations
“…EC-treated ischemic WT mice displayed a reduction of forelimb motor coordination impairments associated with reduced anatomical injury and microglia/macrophage activation in pMCAO and tMCAO models of adult WT mice, impairments which were abolished in tissues and neurons from Nrf2 −/− mice (Shah et al, 2010 ). Interestingly, this neuroprotection was observed in 12 month-old WT and Nrf2 −/− mice, indicating that age influences Nrf2 function (Leonardo et al, 2013 , 2015 ).…”
Section: Nrf2 Targeted Intervention In Ischemic Stroke—advancements Fmentioning
confidence: 95%
“…Multiple lines of evidence demonstrate the beneficial contribution of Nrf2 in various pathological conditions, and most come from studies using Nrf2 knockout (Nrf2 −/− ) or knockdown animals. Reports showed that Nrf2 −/− mice do not exhibit any overt abnormal phenotype regarding size, body weight, food intake, mobility, fertility, or other characteristics at baseline (Itoh et al, 1997 ; Wang et al, 2007 ; Wang Y. C. et al, 2011 ; Wang B. et al, 2012 ; Leonardo et al, 2013 , 2015 ; Doré, 2015 ; Liu et al, 2018 ). In addition, Nrf2 −/− mice exhibit similar cerebrovascular architecture in anastomosis, vascular physiology, and blood pH compared to their WT counterparts (Leonardo et al, 2015 ).…”
Section: Functional Benefit Of Nrf2 In Cerebral Ischemia— Imentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, microglia were considered a homogeneous population, which was supported by the fact that they originated from a uniform progenitor pool that invaded the brain early in development and populated all brain regions. Although differences in morphology between white and gray matter microglia were appreciated in early studies (Del Rio‐Hortega, 1932; Easley‐Neal et al., 2019; Lawson et al., 1990), only recently has there been a renewed interest in understanding microglial heterogeneity. It is becoming clear that microglial distribution differs by brain region and that microglial morphology is remarkably fluid, changing both during physiological conditions and injury.…”
Section: Distinct Subtypes Of Microglia May Have Specific Roles In Different Brain Areas and Developmental Time Periodsmentioning
confidence: 99%
“…This result indicated that Nrf2 modulated protection in the aging phenotype at least in part, but that with aging, the action of Nrf2 is weak. However, EC treatment did not alter microglia activation, vascular permeability or spontaneous hemorrhage [ 31 ].…”
Section: Natural Compounds As Modulator Of Nrf2 Pathway In Stroke mentioning
confidence: 99%